1992
DOI: 10.1007/bf00227668
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear inclusions in paramyxovirus-induced encephalitis: evidence for altered nuclear body differentiation

Abstract: Intranuclear inclusion bodies (INB) are frequently encountered in viral infections, where they are thought to be accumulations of viral particles. However, for RNA viruses replicating in the cytoplasm, this compartmentalization represents a paradox not consistent with the viral replication cycle. To define the basis for intranuclear paramyxoviral inclusion bodies in astrocytes, natural cases of canine distemper virus subacute encephalitis were examined by light and transmission electron microscopy, and by quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Many positive stranded RNA viruses extensively modify and utilize membranes to facilitate their replication, and these have been suggested to represent topologically and functionally related structures (43). Although large intracytoplasmic inclusions are a feature of most paramyxovirus infections and these are generally considered to be the sites of virus replication, membrane rearrangements or vesiculation do not seem to be closely associated with these eosinophilic dense aggregates of viral nucleocapsid (36). We are currently extending these observations by using real-time confocal microscopy to examine the dynamics of the intracellular trafficking of both incoming and newly synthesized polymerases in order to better understand virus assembly and release.…”
Section: Discussionmentioning
confidence: 99%
“…Many positive stranded RNA viruses extensively modify and utilize membranes to facilitate their replication, and these have been suggested to represent topologically and functionally related structures (43). Although large intracytoplasmic inclusions are a feature of most paramyxovirus infections and these are generally considered to be the sites of virus replication, membrane rearrangements or vesiculation do not seem to be closely associated with these eosinophilic dense aggregates of viral nucleocapsid (36). We are currently extending these observations by using real-time confocal microscopy to examine the dynamics of the intracellular trafficking of both incoming and newly synthesized polymerases in order to better understand virus assembly and release.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrathin sections were examined using a Philips 300 transmission electron microscope as previously described. 15 TEM revealed that the perikarya of neurons were distended by fairly uniform vacuoles that contained whorled layers of alternating dense and pale material ( multilayered concentric lamellar bodies ; Fig. 3).…”
mentioning
confidence: 99%